Mind Mapping in A Problem-Based Learning Model to Improve Students' Creative Thinking Skills - Ardiansyah; Toralawe, Yulianti; Gani, Imam Prawiranegara; Alwi, Nurul Maulida (Jurnal Pendidikan dan Pengajaran, 2024)
The low ability of students to think creatively in analyzing problems and the lack of optimal application of learning strategies in Problem Based Learning (PBL) cause students' learning outcomes to not be maximized. This study aims to determine the effect of the application of mind mapping in improving students' creative thinking skills in the PBL learning model. This study uses a pre-experimental design method with a one-group pre-test – post-test design. The population as well as the sample in this study are students of grade XI. The data collection instrument is in the form of a description test given to students before and after learning. The data was analyzed using the average pre-test and post-test scores, normality test, homogeneity test, and one sample T-test. The results of the study show that the application of mind mapping techniques has a significant effect on improving students' creative thinking skills in the PBL learning model. In conclusion, the use of mind mapping helps students understand concepts, improve critical thinking skills, and encourage creativity in problem-solving. This research implies the importance of integrating innovative learning strategies in improving student learning outcomes.